Microbiota-induced regulatory T cells associate with FUT2-dependent susceptibility to rotavirus gastroenteritis - Godefroy, Emmanuelle; Barbé, Laure; Le Moullac-Vaidye, Béatrice; Rocher, Jézabel; Breiman, Adrien; Leuillet, Sébastien; Mariat, Denis; Chatel, Jean-Marc; Ruvoën-Clouet, Nathalie; Carton, Thomas; Jotereau, Francine; Le Pendu, Jacques (Frontiers in Microbiology, 2023)
The FUT2 α1,2fucosyltransferase contributes to the synthesis of fucosylated glycans used as attachment factors by several pathogens, including noroviruses and rotaviruses, that can induce life-threatening gastroenteritis in young children. FUT2 genetic polymorphisms impairing fucosylation are strongly associated with resistance to dominant strains of both noroviruses and rotaviruses. Interestingly, the wild-type allele associated with viral gastroenteritis susceptibility inversely appears to be protective against several inflammatory or autoimmune diseases for yet unclear reasons, although a FUT2 influence on microbiota composition has been observed. Here, we studied a cohort of young healthy adults and showed that the wild-type FUT2 allele was associated with the presence of anti-RVA antibodies, either neutralizing antibodies or serum IgA, confirming its association with the risk of RVA gastroenteritis. Strikingly, it was also associated with the frequency of gut microbiota-induced regulatory T cells (Tregs), so-called DP8α Tregs, albeit only in individuals who had anti-RVA neutralizing antibodies or high titers of anti-RVA IgAs. DP8α Tregs specifically recognize the human symbiont Faecalibacterium prausnitzii, which strongly supports their induction by this anti-inflammatory bacterium. The proportion of F. prausnitzii in feces was also associated with the FUT2 wild-type allele. These observations link the FUT2 genotype with the risk of RVA gastroenteritis, the microbiota and microbiota-induced DP8α Treg cells, suggesting that the anti-RVA immune response might involve an induction/expansion of these T lymphocytes later providing a balanced immunological state that confers protection against inflammatory diseases.